Effectiveness of Various Foliar Fertilizer on the Growth and Performance of Oil Palm (Elaeis guineensis Jacq.) Seedlings in Main Nurseries - Sukmawan, Yan; Riniarti, Dewi (Department of Agronomy and Horticulture, IPB University, 2022)
Fertilizer can be applied through soil and leaves. Fertilizer application through leaves is more effective than soil application due to faster nutrient absorption. This study aims to determine the effectiveness of applying various foliar fertilizer compositions on the growth and performance of oil palm seedlings. The research was conducted from April 2020 to September 2020 at the Oil Palm Nursery Unit at Politeknik Negeri Lampung. A single factor in a completely randomized design with four replications was used in the experiment. The treatment involved the nutrient composition of foliar fertilizer consisting of five levels, namely control (no fertilizer), NPK 20-15-15, NPK 27-18-9, NPK 11-8-6, and NPK 27.5-5.5-4.8. Measurements were made on seedling height, stem diameter, number of leaves, leaf greenness, rachis length, and leaflet length. The data were analyzed by means of variance, followed by orthogonal contrast if the result was significantly different. The results showed that the application of foliar fertilizers could increase the growth of seedling height, stem diameter, number of leaves, leaf greenness index, rachis length, and leaflet length. Generally, a foliar fertilizer application gives better results than without a foliar fertilizer application (control). There was no difference in the powder and liquid foliar fertilizer effect on increasing the growth of oil palm seedlings. The formulation of NPK 20-15-15 and NPK 11-8-6 foliar fertilizer had a better effect on the leaf greenness index of oil palm seedlings.